Spatial-temporal assessment and characterizing urban sprawl for the city of Sulaymaniah-Iraq from 1925-2018 - Hisham Taher Al Jarah, sivan; Zhou, Bo (International Journal of Engineering and Technology, 2018)
Urbanization changes urban landscapes and results in environmental and ecological exhaustion. The dramatic growth of urbanization has been the main controversial concern of many studies due to the passive impacts on the city-built environment. Measuring and characterizing urban sprawl are the main focus of this study. A sequential growth of the city of Sulaymaniah in Iraq has been investigated through quantifying and analyzing the spatial-temporal expansion of the city from 1925 -2018. The study method deviates from triangular method by combining three different approaches; Remote Sensing/GIS, qualitative analysis, and literature review. The study results reveal that Sulaymaniah experienced a tremendous urban pressure especially after 2003, as a result of rapid population growth caused by the enormous migration from other cities of Iraq and neighboring countries, many urban areas have experienced exhaustion of social amenities in the concerned communities. The study findings show that the urban chaos and uncontrolled growth have been an irreversible phenomenon in the structure of the city, likewise, a significance damages have appeared environmentally and ecologically. The outcomes of this study could be a reference point for experts and planners in structuring the new urban growth policies and tools for driving the foreseeable urbanization process which is required in coordinating the future development.